2016
DOI: 10.4102/hts.v72i4.3862
|View full text |Cite
|
Sign up to set email alerts
|

Religion and development: The rise of a bibliography

Abstract: This article endeavours to evidence the extraordinary rise of religion and development as a subject field by presenting a chronological bibliography of the literature that has been published, especially since the early to mid-2000s. By way of introduction and orientation, the authors firstly touch upon existing explanations for the extraordinary new interest in religion and development as a subject field; secondly they comment briefly on the ongoing scholarly endeavour to develop the subject field; and thirdly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…However, the changing social and political contexts have led development thinkers and practitioners to reassess the treatment of religion in development studies and shift in perception toward FBNGOs' activities (Berger, 2003;Clarke, 2008;Haynes, 2013;Lunn, 2009;Swart and Nell, 2016;Tomalin, 2012;Watkinson, 2015). The literature shows some issues that contributed to getting FBNGOs' recognition, such as the global resurgence of religion and identity politics, state policy for supporting FBNGOs, the decline of communism, the failure of a conventional development approach, and the structural adjustment policy including the cutting of welfare budget and placing emphasis on the privatization of welfare services.…”
Section: Trend Of Fbngos In Development Discourse: Nexus Of Modernizamentioning
confidence: 99%
“…However, the changing social and political contexts have led development thinkers and practitioners to reassess the treatment of religion in development studies and shift in perception toward FBNGOs' activities (Berger, 2003;Clarke, 2008;Haynes, 2013;Lunn, 2009;Swart and Nell, 2016;Tomalin, 2012;Watkinson, 2015). The literature shows some issues that contributed to getting FBNGOs' recognition, such as the global resurgence of religion and identity politics, state policy for supporting FBNGOs, the decline of communism, the failure of a conventional development approach, and the structural adjustment policy including the cutting of welfare budget and placing emphasis on the privatization of welfare services.…”
Section: Trend Of Fbngos In Development Discourse: Nexus Of Modernizamentioning
confidence: 99%
“…'Religion and development' has become a well-established research subject area in development studies. From very few articles written on the subject before the millennium (Ver Beek 2000;Wilber and Jameson 1980), selected studies on faith-based organisations as civil society actors (Clarke 2007;Clarke and Jennings 2008) and anthropological work on religion (Bornstein 2003), the literature in the field of 'religion and development' has risen exponentially in the last decade (Olivier 2016;Smith 2017;Swart and Nell 2016;Tomalin 2015). 1 Development studies has now reckoned with the fact that more than 80% of the world's population identifies with a religious group.…”
Section: Introductionmentioning
confidence: 99%
“…This is why community-led initiatives come to the fore. Churches, religious communities, and FBOs have for a long time been engaged in community development ministries and activities side by side with non-governemental organisations (NGOs) and residents' communities (Swart & Nell 2016). The distinctive feature of FBO's community development actions relates to the role of religion and faith as a motivation and a goal for actions (Clarke 2013;Haugen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed growing scholarly interest in religion and development (Swart & Nell 2016). The research has demonstrated the fact that traditional Christian mission churches, despite the ambiguous legacy of colonising evangelisation, have long been active in community development to improve people's lives (eds.…”
Section: Introductionmentioning
confidence: 99%